2008
DOI: 10.1016/j.jvs.2008.02.069
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of intraoperative blood flow measurement with autogenous arteriovenous fistula outcome

Abstract: Intraoperative blood flow measurement is a predictor of the primary and secondary patency of autogenous radiocephalic AVFs. Awareness of the significant correlation between intraoperative AVF blood flow and the short-term outcome would enhance the surgical efficiency and maximize the usefulness of autogenous AVF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
2
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 11 publications
1
31
2
2
Order By: Relevance
“…The greater BFR variability in North America may be one reason why the AVF survival/facility median BFR relationship was stronger in North America than in Japan and EUR/ANZ. It is difficult to assess our results with those published previously which have been variable regarding patient-level BFR and AVF survival [22,23]. However, our study has provided the largest international sample for testing these relationships with detailed and extensive adjustments to allow greater generalizability and greater ability to account for treatment-by-indication bias.…”
Section: Discussionmentioning
confidence: 92%
“…The greater BFR variability in North America may be one reason why the AVF survival/facility median BFR relationship was stronger in North America than in Japan and EUR/ANZ. It is difficult to assess our results with those published previously which have been variable regarding patient-level BFR and AVF survival [22,23]. However, our study has provided the largest international sample for testing these relationships with detailed and extensive adjustments to allow greater generalizability and greater ability to account for treatment-by-indication bias.…”
Section: Discussionmentioning
confidence: 92%
“…Women may present with smaller-caliber arteries and may therefore be expected to have lower AVF patency rates than men. However, Caplin et al 4 showed that arterial and venous diameters 39,40 Yes Can be used as prognostic tool or prompt re-evaluation in short-term benefit but paucity of data/largest trial found reduced thrombosis rate but no effect on cumulative patency…”
Section: Patient Factorsmentioning
confidence: 99%
“…39 A prior report correlated flows of Ͻ200 mL/min with reduced primary and secondary patency. 40 AVFs with low flows after anastomosis could therefore be identified as "at risk" and may thus warrant further investigation in the theatre or by more intensive follow-up regimens.…”
Section: Intraoperative Factorsmentioning
confidence: 99%
“…Preoperative duplex scan-derived mean volume flows (VFs) 20 and highest PSVs at the most significant stenosis were recorded and compared with postoperative findings.…”
Section: Patientsmentioning
confidence: 99%